2013
DOI: 10.1371/journal.pone.0081811
|View full text |Cite
|
Sign up to set email alerts
|

A RabGAP Regulates Life-Cycle Duration via Trimeric G-protein Cascades in Dictyostelium discoideum

Abstract: BackgroundThe life-cycle of cellular slime molds comprises chronobiologically regulated processes. During the growth phase, the amoeboid cells proliferate at a definite rate. Upon starvation, they synthesize cAMP as both first and second messengers in signalling pathways and form aggregates, migrating slugs, and fruiting bodies, consisting of spores and stalk cells, within 24 h. In Dictyostelium discoideum, because most growth-specific events cease during development, proliferative and heterochronic mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The reported small GTPases downstream of these GEFs are Rap1 and Rap2, and thus we tested their potential involvement by dominant negative and constitutively active Rap proteins ( Fu et al, 2007 ). None of these showed obvious effects on the Htt lowering by Gpr52 knock-down ( Figure 3—figure supplement 3 ), suggesting novel mechanisms potentially involving other GEFs and/or small GTPases, which is suggested in other models as well ( Emery and Eiden, 2012 ; Kuwayama et al, 2013 ). Given that the major function of small GTPases is trafficking, we tested potential Htt translocation events upon treatments of PKA-insensitive analogs Rp-cAMP or 8-pCPT-2′-O-Me cAMP, and found that they lead to Htt enrichment at the perinuclear regions and co-localization with the endoplasmic reticulumn (ER) marker ( Figure 3E ).…”
Section: Resultsmentioning
confidence: 90%
“…The reported small GTPases downstream of these GEFs are Rap1 and Rap2, and thus we tested their potential involvement by dominant negative and constitutively active Rap proteins ( Fu et al, 2007 ). None of these showed obvious effects on the Htt lowering by Gpr52 knock-down ( Figure 3—figure supplement 3 ), suggesting novel mechanisms potentially involving other GEFs and/or small GTPases, which is suggested in other models as well ( Emery and Eiden, 2012 ; Kuwayama et al, 2013 ). Given that the major function of small GTPases is trafficking, we tested potential Htt translocation events upon treatments of PKA-insensitive analogs Rp-cAMP or 8-pCPT-2′-O-Me cAMP, and found that they lead to Htt enrichment at the perinuclear regions and co-localization with the endoplasmic reticulumn (ER) marker ( Figure 3E ).…”
Section: Resultsmentioning
confidence: 90%
“…Full‐length gmf A was amplified with a cDNA mixture prepared from aggregation‐stage mRNA using an oligo‐dT primer and verified by sequencing. To construct the overexpression and fluorescent protein fusion vectors, the full‐length gmf A cDNA was fused with the HA‐tag sequence (YPYDVPDYA) at the 5′‐region by PCR and cloned into the cloning site of the expression vector pHK12neo‐N‐Venus [ 52 ]. The expression vector of GFP‐Arp3 was obtained from NBRP Nenkin [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The amplified fragment was verified by sequencing. For constructing the overexpression mutant, the full‐length Dd dhkC cDNA was cloned into the cloning site of pHK12neo . After transformation, a neomycin‐resistant clone was isolated as a dhkC overexpression mutant (designated dhkC OE ).…”
Section: Methodsmentioning
confidence: 99%
“…Reverse transcription‐polymerase chain reaction (RT‐PCR) amplification of dhkC was performed as described previously , by using the DNA primers 5′‐TTATCACCAAGAGCCCCAAC‐3′ and 5′‐AATTGAGCAACGGCTTTCTC‐3′.…”
Section: Methodsmentioning
confidence: 99%